Desarrollo de un módulo para la gestión de prácticas preprofesionales de la Universidad Nacional de Loja - Guaman Sarango, Brayan Marco (2025)
Currently, at the National University of Loja, pre-professional internships are not centralised, which means that each degree programme manages them independently. This means that each degree programme manages its own repositories and processes, which generates multiple different formats. As a result, there are problems related to the streamlining of key processes, such as the generation of letters of commitment, agreements, planning, development and evaluation of pre-professional internships, among others. This Curricular Integration Work was developed based on the solution of the aforementioned problems. For this purpose, a management module was developed for pre-professional internships that allows the centralisation of all the processes involved in pre-professional internships: work placements and community service internships. The work was based on the university’s current regulations and on constant communication with the Directorate of Social Relations of the National University of Loja, which is responsible for the pre-professional internship area. The module will be integrated into the Academic Administrative Financial Information System (SIAAF), and was developed under the guidelines established by the Directorate of Information Technology (DTI) of the university. The Extreme Programming (XP) methodology was implemented, Model-View-Template architecture and the requirements specification was carried out under the IEEE 830 standard. At the culmination of the Curriculum Integration Work, several tests were performed, including unit, integration and acceptance tests. Finally, the functionality of the module was evaluated within a controlled environment, which allowed us to conclude that the development of a management module for pre-professional internships does optimise the processes of pre-professional internships within the National University of Loja. Keywords: Pre-professional internships, XP, IEEE 830, IEEE 1471-2000.